The effectiveness of capacity markets in the presence of a high portfolio share of renewable energy sources - Pradyumna C. Bhagwat; Kaveri K. Iychettira; Jörn C. Richstein; Emile J.L. Chappin; Laurens J. De Vries (Utilities Policy, 2017)
The effectiveness of a capacity market is analyzed by simulating three conditions that may cause suboptimal investment in the electricity generation: imperfect information and uncertainty; declining demand shocks resulting in load loss; and a growing share of renewable energy sources in the generation portfolio. Implementation of a capacity market can improve supply adequacy and reduce consumer costs. It mainly leads to more investment in low-cost peak generation units. If the administratively determined reserve margin is high enough, the security of supply is not significantly affected by uncertainties or demand shocks. A capacity market is found to be more effective than a strategic reserve for ensuring reliability.
Keywords: 330; Adequacy policy; Security of supply; Capacity markets